'This is not part of my life plan': A qualitative study on the psychosocial experiences and practical challenges in young adults with cancer age 25 to 39 years at diagnosis. (3rd May 2021) - Lidington, Emma; Vlooswijk, Carla; Stallard, Kate; Travis, Emily; Younger, Eugenie; Edwards, Penelope; Nandhabalan, Meera; Hunter, Nikki; Sarpal, Neelam; Flett, Denise; Din, Amy; Starling, Naureen; et al.
Abstract: Objective: Adolescents and young adults with cancer face unique psychosocial and practical issues. However, patients across this group encounter different life experiences, cancer diagnoses and treatment settings given the tailored services for patients ages 15 to 24. Here, we qualitatively explore the psychosocial experiences and practical challenges of young adults (YAs) with cancer diagnosed between ages 25 and 39 in the United Kingdom. Methods: We invited YAs diagnosed with cancer in the 5 years prior to enrolment at participating sites to take part in semi‐structured interviews or focus groups. Transcripts were analysed using inductive thematic analysis. Two YA patients reviewed the results to ensure robustness. Results: Sixty‐five YAs with varied diagnoses participated. Participants struggled to balance work, childcare and financial solvency with treatment. The halt in family and work life as well as changes in image and ability threatened participants' identity and perceived 'normality' as a YA, however, these also stimulated positive changes. YAs experienced social isolation from friends and family, including children. Many struggled to cope with uncertainty around treatment outcomes and disease recurrence. Conclusion: The disruption of family and work life can lead to age‐specific issues in YAs diagnosed with cancer. Age‐tailored psychological and practical services must be considered.